Living in Biological Darkness: Objective Sleepiness and the Pupillary Light Responses Are Affected by Different Metameric Lighting Conditions during Daytime. Issue 4 (August 2019) - de Zeeuw, Jan; Papakonstantinou, Alexandra; Nowozin, Claudia; Stotz, Sophia; Zaleska, Mandy; Hädel, Sven; Bes, Frederik; Münch, Mirjam; Kunz, Dieter
Nighttime melatonin suppression is the most commonly used method to indirectly quantify acute nonvisual light effects. Since light is the principal zeitgeber in humans, there is a need to assess its strength during daytime as well. This is especially important since humans evolved under natural daylight but now often spend their time indoors under artificial light, resulting in a different quality and quantity of light. We tested whether the pupillary light response (PLR) could be used as a marker for nonvisual light effects during daytime. We also recorded the wake electroencephalogram to objectively determine changes in daytime sleepiness between different illuminance levels and/or spectral compositions of light. In total, 72 participants visited the laboratory 4 times for 3-h light exposures. All participants underwent a dim-light condition and either 3 metameric daytime light exposures with different spectral compositions of polychromatic white light (100 photopic lux, peak wavelengths at 435 nm or 480 nm, enriched with longer wavelengths of light) or 3 different illuminances (200, 600, and 1200 photopic lux) with 1 metameric lighting condition (peak wavelength at 435 nm or 480 nm; 24 participants each). The results show that the PLR was sensitive to both spectral differences between metameric lighting conditions and different illuminances in a dose-responsive manner, depending on melanopic irradiance. Objective sleepiness was significantly reduced, depending on melanopic irradiance, at low illuminance (100 lux) and showed fewer differences at higher illuminance. Since many people are exposed to such low illuminance for most of their day—living in biological darkness—our results imply that optimizing the light spectrum could be important to improve daytime alertness. Our results suggest the PLR as a noninvasive physiological marker for ambient light exposure effects during daytime. These findings may be applied to assess light-dependent zeitgeber strength and evaluate lighting improvements at workplaces, schools, hospitals, and homes.